The application of anticoagulant therapy to sepsis - Jecko Thachil; Toshiaki Iba (Journal of Intensive Care, 2017)
Abstract Since the withdrawal of recombinant-activated protein C, the anticoagulant therapy for sepsis was taken no notice. For instance, the international sepsis guidelines did not share a space for this therapy. However, we can see the signs of change recently. The Surviving Sepsis Campaign Guidelines 2016 introduced the development of recombinant thrombomodulin, and the European Society of Intensive Care Medicine released comments on this subject. However, since small but important discrepancy was recognized between the standpoints of Japan (more aggressive) and other countries (rather conservative), we intend to discuss on this point.